Epigenetic control of early neurodegenerative events in diabetic retinopathy by the histone deacetylase SIRT6. Issue 2 (21st November 2017) - Zorrilla‐Zubilete, María A.; Yeste, Ada; Quintana, Francisco J.; Toiber, Debra; Mostoslavsky, Raul; Silberman, Dafne M.
Abstract: Diabetic retinopathy (DR) is one of the common complications associated with diabetes mellitus and the leading cause of blindness worldwide. Recent research has demonstrated that DR is not only a microvascular disease but may be a result of neurodegenerative processes. Moreover, glucose‐induced neuron and glial cell damage may occur shortly after the onset of diabetes which makes the disease hard to diagnose at early stages. SIRT6, a NAD‐dependent sirtuin deacylase, modulates aging, energy metabolism, and neurodegeneration. In previous studies we showed that SIRT6 deficiency causes major retinal transmission defects, changes in the expression of glycolytic genes, and elevated levels of apoptosis. Given the importance of glucose availability for retinal function and the critical role of SIRT6 in modulating glycolysis, we aimed to analyze SIRT6 participation in the molecular machinery that regulates the development of experimental DR. Using non‐obese diabetic mice, we determined by western blot that 2 weeks after the onset of the disease, high glucose concentrations induced retinal increase in a neovascularization promoting factor (vascular endothelial growth factor, VEGF), and the loss of a neuroprotective factor (brain‐derived neurotrophic factor, BDNF) associated with reduced levels of SIRT6 and increased acetylation levels of its substrates (H3K9 and H3K56) suggesting a deregulation of key neural factors. Noteworthy, retinas from CNS conditionally deleted SIRT6 mice showed a resemblance to diabetic retinas exhibiting lower protein levels of BDNF factor and increased protein levels of VEGF. Moreover, cultured Müller glial cells subjected to high glucose concentrations exhibited decreased levels of SIRT6 and increased levels of H3K56 acetylation. In addition, the increment of VEGF levels induced by high glucose was reverted by the over‐expression of SIRT6 in this cell type. Accordingly, siRNA experiments showed that, when SIRT6 was silenced, VEGF levels increased. Our findings suggest that epigenetically regulated neurodegenerative events may occur at an early diabetic stage prior to the characteristic proliferative and vascular changes observed at a later diabetic stage. Abstract : Diabetic Retinopathy is not only a microvascular disease but a result of neurodegenerative processes. SIRT6 is a NAD‐dependent histone deacetylase that modulates glucose metabolism and neurodegeneration. We demonstrated that high glucose concentrations induced a reduction in retinal SIRT6 levels associated with increased acetylation levels of its substrates (H3K9 and H3K56) that in turn promotes an increase in the vascular endothelial growth factor (VEGF) and a decrease in the brain‐derived neurotrophic factor (BDNF) suggesting that epigenetically regulated neurodegenerative events may occur prior to the vascular changes observed at a later diabetic stage.